Year in Review: Synopsis of Selected Articles in Neuroanesthesia and Neurocritical Care from 2024 - Imaan A. Rahim; Maria C. Solorzano Aldana; Aishvarya S. Nedunchezhian; Lashmi Venkatraghavan (Journal of Neuroanaesthesiology and Critical Care)
This review is a synopsis of selected articles from neuroscience, neuroanesthesia, and neurocritical care from 2024 (January–November 2024). The journals reviewed include anesthesia journals, critical care medicine journals, neurosurgical journals, and high-impact medical journals such as the Lancet, Journal of American Medical Association, New England Journal of Medicine, and Stroke. We identified articles that are randomized clinical trials, large retrospective and prospective observational studies, systematic reviews, and meta-analysis relevant to clinical neuroanesthesia and neurocritical care practice. We excluded the basic science research articles, case reports, and case series. The summary of important articles will serve to update the knowledge of neuroanesthesiologists and other perioperative physicians who provide care to neurosurgical and neurocritical cases.